Ernsta Glika nopelni-pirmā bībele latviešu valodā un skolas Vidzemē - Baltaisbrence, Jana (Latvijas Universitāte, 2009)
Meklējot darbu E. Gliks 1673. gadā ieradies Vidzemē un 1683. gadā Marienburgā (Alūksnē). Darbības laikā šeit viņš savu spēku veltīja latviešu zemnieku skolu izveidei, Bībeles un citu garīgo rakstu tulkojumam, kā arī latviešu literārās valodas izveidei. E. Gliks veicis Jaunās Derības tulkojumu 1685. gadā, bet Veco Derību iztulkojis 1689. gadā. Šim vēsturiski nozīmīgajam darbam par godu viņš pie mācītājmājas iestādījis divus ozolus, kas zaļo vēl šodien. Kā mācītājs , bet vēlāk - Kokneses apriņķa prāvests uzcītīgi vadījis draudzes. No vēstulēm un ziņojumiem, bet īpaši 1699. gadā rakstītās vēstules ģenerālgubernatoram Dālbergam par iepriekšminētajiem faktiem iespējams uzzināt vēl precīzāk. Semestra darba mērķis – atrast, izpētīt un apkopot pēc iespējas vairāk E. Glika materiālu – dokumentāro liecību par 17. gs. b. Vidzemes kultūrvēsturisko un sociālo gaisotni.

In search for work, in 1673 E. Glick arrived in Vidzeme for the first time and in 1683 he arrived in Marienburg (Alūksne). During his active work starting from 1683, he devoted his energy for establishing Latvian peasant schools in Vidzeme; translating the Bible, the Little Catechism and other sacred texts, as well as for the formation of Latvian literary language. E .Glick translated the New Testament in 1685, and the Old Testament in 1689. In honour of this historically remarkable event he planted two oaks near the vicarage in Marienburg, which are growing there at present as well. As a priest, and later also as a dean of Koknese region he diligently worked in several parishes in Vidzeme. The authors of the book „Ernst Glick (1654-1705) Priest, linguist, promoter of Enlightenment in Baltic countries and Russia” have successfully made the original texts of Ernst Glick available for the public at large. It gives understanding about his language style, ability to argue, his political, religious and moral values. The manuscripts of E. Glick, as far as it is known, can be found in archives in Sweden, Germany and Russia. The Aim of the Diploma Paper – to find, research and collect as many materials about Ernst Glick – the documentary statements about the cultural mood in Vidzeme at the end of 17th century.
Ernst Gluck's Distributions - the First Bible in the Latvian Language and Schools in Livonia
Keywords: Vācu filoloģija